Pendampingan Membaca Al-Qur'an Sebelum Belajar Melalui Kegiatan Pengabdian Mahasiswa IAIN Palangka Raya - Nabila Khairunnisa Wahdarohmah; Abdullah Abdullah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Strengthening students' spirituality is one of the main goals achieved in Islamic education through various religious activities, which also provide opportunities for MBKM IAIN Palangka Raya students to apply the knowledge gained on campus. In this context, this research focuses on the Al-Qur'an tadarus mentoring program at MAN Palangka Raya City, which aims to increase student participation in reading the Al-Qur'an before learning. Mentoring is carried out by students from the Independent Learning Campus (MBKM) Teaching Assistance program with a Service Learning (SL) approach, which involves students in direct experiences that are beneficial for students. This activity was carried out at MAN Palangka Raya City using the congregational tadarus method. The results of this service show that student participation in tadarus activities increased significantly after mentoring, with students who previously were often late starting to show better discipline and increased awareness of the importance of tadarus as spiritual preparation before studying. This program succeeded in creating a more religious and conducive classroom atmosphere.